The Differences In Nutritional Status Based On The Use Of Online Food Delivery (OFD) Services Among The University of Indonesia's Non-Health Science Cluster Students In 2023 - Muhammad Aulia Rizky; Asih Setiarini; Sandra Fikawati; Fajrinayanti . (Faculty of Public Health Universitas Indonesia, 2023)
Uncontrolled use of Online Food Delivery (OFD) can increase food intake and affect the incidence of overweight/obesity. This study aims to examine the differences in the proportion of nutritional status based on the use of OFD services among UI non-health science cluster students. This study involved 136 respondents using a purposive sampling method and cross-sectional study design. Data were collected through anthropometric measurements, Google Form, and direct interviews to be analyzed by Chi-Square test and multiple logistic regression. The results showed significant differences in the proportion of nutritional status based on the duration of consumer loyalty, pocket money, and energy intake. After controlling for physical activity and energy intake, there was a difference in the proportion of nutritional status based on food preference with a negative relationship (p-value = 0.039; OR = 0.213; 95% CI = 0.49-0.93). Energy intake was the dominant factor influencing food preferences on nutritional status (OR = 9.605, 95% CI). Further research is needed to consider other aspects of OFD use and nutritional status. Non-health science cluster UI students are advised to pay attention to balanced nutrition messages in food selection when using OFD to avoid the risk of overnutrition or obesity.